At the crossroads of religion and palliative care in patients with dementia - Kieran L. Quinn; Daphna L. Grossman (BMC, 2020)
Abstract The timing of palliative care initiation may be more appropriately directed using a needs-based approach, instead of a prognostically driven one. Jewish Law or Halachah ("the way") upholds a strong commitment to the sanctity of life and teaches that the duty to prolong life supersedes the duty to end suffering prematurely, unless one is expected to imminently die. This intersection of palliative care and a reliance on prognostic triggers with an individual's observance of religious traditions complicates matters nearing the end-of-life. A recent pilot study by Sternberg et al. of 20 patients with advanced dementia in Israel found that home hospice care significantly reduced distressing symptoms, caregiver burden and hospitalization and teaches us important lessons about some of the essential elements to providing excellent palliative care at home, including the 24/7 availability of healthcare providers outside of the emergency department. In light of specific religious practices, palliative care should strive to incorporate a patient's specific religious observance as part of high-quality end-of-life care.